2014
DOI: 10.1097/opx.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Color Vision Deficiency in Zahedan, Iran

Abstract: The prevalence of red-green color vision deficiency was found to be significantly lower in Zahedan than comparable reports in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…The prevalence of color blindness was 15.85% in men and 12.96% in women. Although other studies have also reported a higher prevalence of the disease in men versus women,1, 23, 24, 25, 26, 27, 28, 31, 33 the prevalence of color blindness in our female participants was higher than other studies. Although this finding is in line with the findings of study, 1 other previous studies have not supported this finding 7, 8, 18, 19, 20, 23, 24, 25, 26, 28, 32, 33…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The prevalence of color blindness was 15.85% in men and 12.96% in women. Although other studies have also reported a higher prevalence of the disease in men versus women,1, 23, 24, 25, 26, 27, 28, 31, 33 the prevalence of color blindness in our female participants was higher than other studies. Although this finding is in line with the findings of study, 1 other previous studies have not supported this finding 7, 8, 18, 19, 20, 23, 24, 25, 26, 28, 32, 33…”
Section: Discussioncontrasting
confidence: 95%
“…It seems that Mashhad, as one of the most religious cities of Iran, has a similar condition leading to an increase in CVD. The differences between our study and the studies conducted in other parts of Iran confirm this hypothesis 19, 20, 32, 33…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, studies in the nearby countries found that the prevalence of color vision deficiency was: 8.72% of males and 0.33% of females (n=1418, 218 males and 1200 females) in Jordan 20 , 7.33% among the Turkish males (n=941 males) 21 , 5.85% of males and 0.75% of females (n=1638, 838 males and 800 females) among the Saudi Arabia children 22 , and 1.6% of males, 0.2% of the females (n=1000) in Zahedan, Iran 23 which is obviously lower than predicted. The prevalence of color vision deficiency among the males and females in the present study is higher than prevalence rates in the above countries and higher than the global range, which is near 8% in boys and 0.4% in girls of Caucasians ethnic group 3-15-24 and between 4% and 6.5% in males and 0.7% and 1.7% in females of Japanese and Chinese ethnicities 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, previous studies showed that the prevalence of acquired CVD is higher in the population above 40 years of age [21] . Few studies in Iran reported the prevalence of CVD between 1.6% and 15.85% depending on demographic factors [18,[22][23] . For example, the Shahroud Eye Cohort study reported the prevalence of acquired and congenital CVD as 1.1% and 4.4%, respectively [18] .…”
Section: Introductionmentioning
confidence: 99%